Caracterização da participação de crianças brasileiras com desenvolvimento típico e investigação de possíveis preditores de participação - Zanata, Mariana (UFSCar, 2026)
Introduction: Participation has received increasing attention in the field of pediatric rehabilitation since its inclusion as a core component of the International Classification of Functioning, Disability and Health (ICF). Participation can be defined by two main concepts: attendance and involvement. Although participation is an important domain for assessment, goal setting, and intervention due to its role in promoting child development and quality of life, studies investigating participation among children with and without disabilities remain scarce in Brazil and worldwide. Furthermore, there are still gaps in the literature regarding the understanding of environmental factors that influence participation, given its strong contextual nature. Objectives: To characterize participation and participation-related environmental factors among Brazilian children with typical development in the home, school, and community settings; to investigate sex differences; and to identify potential predictors of participation. Materials and Methods: This cross-sectional study included parents of children with typical development aged 6 to 10 years enrolled in public schools in the state of Santa Catarina, Brazil. Data were collected as part of a larger study that aimed to evaluate the participation of children with evelopmental Coordination Disorder (DCD) compared with their typically developing peers. The study was approved by the Ethics Committee of the Federal University of São Carlos (CAAE: 55391722.5.0000.5504). A questionnaire developed by the researchers was used to characterize the sample, and participation and environmental factors were assessed using the Participation and Environment Measure for Children and Youth (PEM-CY). Descriptive analyses were conducted for frequency, involvement, number of activities, and overall environmental support across home, school, and community settings. Data normality was assessed using the Shapiro–Wilk test. Differences in participation patterns according to sex were analyzed using the Mann–Whitney test, and participation determinants were investigated through regression analyses. Statistical significance was set at 5% (p < 0.05). Results: High participation frequency was observed at home (M = 6.3) and at school (M = 5.0), while participation frequency in the community was moderate (M = 4.0). Involvement was high across all three settings (M = 4.0, 4.0, and 5.0, respectively). The number of activities was lower in the community, with a median participation in 6 out of 10 assessed activities. Desire for change was frequently reported across all settings. Overall environmental support was high, although it was perceived as lower in the community, where more barriers were also identified. Significant sex differences were found in involvement at school (p = 0.002) and in the community (p = 0.012), with girls demonstrating higher levels of involvement. Among the 12 regression models tested, only the model for desire for change at school was significant (p = 0.012), with perceived school barriers being the only significant predictor of this outcome (p = 0.012). Conclusion: Children with typical development demonstrated high levels of participation frequency and involvement at home and at school, and moderate participation frequency in the community. Sex differences were observed in involvement within the school and community settings. Overall, the findings are consistent with the international literature and provide reference data for comparisons with clinical populations in Brazil. Furthermore, the perception of greater barriers within the school environment was associated with a stronger parental desire for changes in their children's participation, highlighting the importance of considering environmental factors in interventions aimed at promoting children's participation.
Participation among brazilian children with typical development: characterization and investigation of potential predictors
Keywords: Participação; Crianças; Desenvolvimento Típico; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar